Analisis Kinerja Pengelolaan Aset Daerah dan Sumber Daya Manusia di BPPKAD Kabupaten Magelang - Daffa Lanang Pradana; Umi Sulistiyanti (Jurnal Riset Akuntansi, 2023)
Management of regional property is a very important element because it represents assets owned by the region and is supervised by the local government. Through effective asset management by local governments, all regional properties can be managed and utilized well. In accordance with Government Regulation Number 28 of 2020, State/Regional Property refers to things obtained or purchased using funds from the State/Regional Revenue and Expenditure Budget, as well as those obtained through other legal means. Macro human capital refers to a country's total workforce, encompassing individuals who have reached the age at which they are eligible to work, which includes both those already employed and those actively seeking work but still unemployed. Micro human resources refer to individuals who are part of the workforce within a company or organization, including workers and volunteers, who constitute the workforce of a company or organization.